THE USE OF GUIDED COMPOSITION TO ENHANCE THE ABILITY IN WRITING OF SECOND SEMESTER STUDENTS OF PURWOREJO MUHAMMADIYAH UNIVERSITY IN THE ACADEMIC YEAR OF 2015/2016 - Puspa Dewi (p-ISSN 2356-0576, 2016)
Abstract: The purpose of this study is to describe whether guided composition is effective or not to improve students’ ability in writing at the seconds semester students of English Education Program of Purworejo Muhammadiyah University. It is an experimental research. There are 72 students joining the research where 36 students are in experimental group and the other 36 students are in control group. In the purpose of having good ability of communication both in spoken and written English, nonnative  students do writing. The lecturer can use various teaching strategies. Guided writing is considered an effective tool  in helping learners put words down on paper. Moreover, guided writing strategy is a teaching strategy which is valuable to expand and develop texts in written form during writing.The research findings showed that guided composition is effective to improve students’ ability in writing. It can be seen from the mean score of pre-test and post-test from both experimental group (65.03 and 76.06) and control group (64.03 and 65.33). In addition, the result of t-test is 5.703 with the significance level of 5%. Key words: guided composition, teaching, writing Abstrak: Tujuan dari penelitian ini yaitu untuk mengetahui apakah strategi guided composition efektif atau tidak untuk meningkatkan kemampuan menulis mahasiswa semester dua program studi pendidikan Bahasa Inggris Universitas Muhammadiyah Purworejo. Penelitian ini menggunakan metode eksperimen dimana ada 72 mahasiswa sebagai sampel yang terdiri dari 36 mahasiswa dikelompok ekperimen dan 36 mahasiswa dikelompok kontrol.Dalam upaya mempunyai kemampuan berkomunikasi yang baik dalam bahasa lisan maupun tulis, mahasiswa melakukan kegiatan menulis. Pengajar dapat menggunakan berbagai strategi dalam mengajar di kelas. Guided wirting merupakan salah satu strategi mengajar yang dinilai efektif untuk membantu para mahasiswa menulis. Terlebih lagi, guided compositionmerupakan strategi mengajar yang penting untuk mengembangkan gagasan kedalam sebuah teks. Berdasarkan hasil penelitian, guided composition merupakan strategi yang efektif dalam mengajarkan menulis pada mahasiswa. Hal ini dapat dilihat dari pemerolehan nilai mean terhadap pre test dan post test baik dari kelompok eksperimen(65.03 dan 76.06) dan kelompok kontrol (64.03 dan 65.33). Hasil t-tes menunjukkan angka 5.705 lebih besar dari t-tabel 1.99. Hal ini dapat disimpulkan bahwa penggunaan strategi guided composition efektif untuk mengajar kelas menulis pada mahasiswa semester 2 program studi pendidikan Bahasa Inggris Universitas Muhammadiyah Purworejo.   Kata kunci: guided composition, pengajaran, menulis